(untitled) (World Bulletin of Social Sciences, 2021)
The article provides a scientific analysis of the formation of the Chaganian state, theoretical and practical views on its development, discussions on this issue, the spiritual foundations of the first statehood, which is of particular importance in the history of Uzbek statehood